Implementasi Media Love Alarm Puzzle terhadap Kepatuhan Minum Obat Malaria - Mardona, Yeli; Diliani, Diliani; Tanan, Rosmitha; Firman, Andi Fatmawati; Karundeng, Jeni Oktavia (Journal of Telenursing (JOTING), 2024)
This study aims to explore the benefits of the Love Alarm Puzzle media with compliance in taking malaria medication in SP 6 Village, Naena Muktipura Village, Iwaka District, Mimika Regency. The method used is descriptive qualitative with purposive sampling technique. Based on the theme analysis, the results of the study showed that the cause of non-compliance in taking malaria medication was due to forgetfulness and the benefits of implementing the love alarm puzzle media were increased compliance in taking malaria medication. The conclusion after this implementation was carried out, compliance in taking malaria medication in patients increased. Keywords: Love Alarm Puzzle, Malaria